Pengaruh Disiplin Kerja Dan Fasilitas Kerja Terhadap Kinerja Pegawai Sekretariat Daerah Kota Depok - Wira Tria Nita; Irwan Raharja (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This study aims to explain the partial and simultaneous influence between work discipline variables and work facilities on employee performance in the Depok City Regional Secretariat. Problems that occur regarding work discipline, work facilities, so that it can interfere with employee performance. This type of research is quantitative research because it leads to measurement methods and samples to test variables and hypotheses. Data processing using the SPSS program version 27, researchers conducted several tests including validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, t tests, F tests, multiple linear regression analysis and determination coefficient tests. The population in this study amounted to all employees of the Depok City Regional Secretariat, the research sample was 50 people and all permanent employees were used as research samples (saturated samples). The results of this study obtained that work discipline has a partial and significant effect on employee performance. Work facilities have a partial and significant effect on employee performance. Work Discipline and Work Facilities simultaneously affect employee performance